2018
DOI: 10.3389/fimmu.2017.01966
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Vaccination in HIV-1-Infected Young Adults: A Tool to Reduce the Size of HIV-1 Reservoirs?

Abstract: During anti-retroviral therapy (ART) HIV-1 persists in cellular reservoirs, mostly represented by CD4+ memory T cells. Several approaches are currently being undertaken to develop a cure for HIV-1 infection through elimination (or reduction) of these reservoirs. Few studies have so far been conducted to assess the possibility of reducing the size of HIV-1 reservoirs through vaccination in virologically controlled HIV-1-infected children. We recently conducted a vaccination study with a combined hepatitis A vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…ART administration has a positive impact on a variety of clinical symptoms associated with HIV-1 infection in children [ 1 ]. However, ART provided during the chronic phase of HIV-1 infection in children has ameliorated, but not reversed, abnormal features of immune activation [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…ART administration has a positive impact on a variety of clinical symptoms associated with HIV-1 infection in children [ 1 ]. However, ART provided during the chronic phase of HIV-1 infection in children has ameliorated, but not reversed, abnormal features of immune activation [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bekele et al demonstrated the influence of HBV vaccination in affecting the size of HIV reservoirs in 22 HIV-infected children. They showed that total HIV DNA levels after both hepatitis A virus (HAV) and HBV vaccination were reduced compared to baseline, although the decline was not statistically significant [ 19 ]. The influence of HBV vaccination in the size of the HIV reservoir in PLWHs has not been well evaluated.…”
Section: Introductionmentioning
confidence: 99%